Prentisstown's Institution Life Described in Patrick Ness's Novel "The Knife of Never Letting Go" - Achmad Kamal; Haryati Sulistyorini (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2019)
This thesis entitled Prentisstown's institution life described in Patrick Ness's Novel "THE KNIFE OF NEVER LETTING Go". This study is aimed to observing Prentisstown's insitution life truogh the general description and conflict of Todd as the main character and also the setting, and the institution life of Prentisstown. The researcher used decriptive qualitative method during this research since the aim of this study is to observed Prentisstown's institution life. The main character in this novel experiences some conflicts such as; as he was worried, frustrated, confused, and anxious with himself, and against Ben, Aaron, Mayor Prentiss, Mr. Prentiss Jr, Viola, Matthew, Prentisstown menâ€™s noises, and his knife. The setting of time that related to conflict are in the morning and at the night. Then, the setting of place that related to conflicts areÂ  Prentisstown, Toddâ€™s house, Swamp, Spackle buildings, Bridge, Farbranch, Brockle Falls, Woods, Carbonel Down, Ledge, and Haven. The setting of social of Todd HewittÂ  was a low class. Finally, The institution life in Prentisstiown has social structures such as mayor, advisor, the right hand of mayor, horseback armies and prentisstown armies. Those people has a norms such as Restriction against the books and teaching, men should kill the women, the tradition of boy become a man, and the symbol of the last boy in Prentisstown.Keywords : Institution life, Norms, Social stuctures, Sociology.